Bydgoszcz 1920. Wojsko w niepodległym mieście (Kronika Bydgoska, 2018)
The article describes activities of the Polish Army conducted when Bydgoszcz was taken over in January 1920. It tells about preparations to a solemn homecoming ceremony and organization of barracks to accommodate Polish soldiers. The author writes about a cautious approach to this issue by the Bydgoszcz residents, considering the fact that the majority of them included an uncertain German population. This may have caused a number of tensions between both nations, thus attempts were being made to prevent them by issuing military decrees. The article further describes the first two weeks in the liberated city and difficulties related to provisioning.